Collaborative interactions of heterogenous ribonucleoproteins contribute to transcriptional regulation of sterol metabolism in mice - Zhang, Zhengyi; Feng, An-Chieh; Salisbury, David; Liu, Xin; Wu, Xiaohui; Kim, Jason; Lapina, Irina; Wang, Dan; Lee, Brennan; Fraga, Josue; Pan, Calvin; Williams, Kevin J.; et al. (Nature communications, 2020)
Heterogeneous nuclear ribonucleoproteins (hnRNPs) are a group of functionally versatile proteins that play critical roles in the biogenesis, cellular localization and transport of RNA. Here, we outline a role for hnRNPs in gene regulatory circuits controlling sterol homeostasis. Specifically, we find that tissue-selective loss of the conserved hnRNP RALY enriches for metabolic pathways. Liver-specific deletion of RALY alters hepatic lipid content and serum cholesterol level. In vivo interrogation of chromatin architecture and genome-wide RALY-binding pattern reveal insights into its cooperative interactions and mode of action in regulating cholesterogenesis. Interestingly, we find that RALY binds the promoter region of the master metabolic regulator Srebp2 and show that it directly interacts with coactivator Nuclear Transcription Factor Y (NFY) to influence cholesterogenic gene expression. Our work offers insights into mechanisms orchestrating selective promoter activation in metabolic control and a model by which hnRNPs can impact health and disease states. Heterogeneous nuclear ribonucleoproteins (hnRNPs) play critical roles in the biogenesis, localization and transport of RNA. Here authors investigate a role for hnRNPs in sterol metabolism in mice and provide insights into their role in selective promoter activation.